Dietry and lifestyle changes of Malaysia breast cancer survivors: a qualitative study - A.A Redhwan,; M.N Md. Idris,; C Robert, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Objective : This study was performed to determine changes in diet and lifestyle among breast cancer survivors in Malaysia. Methods : This was a qualitative study done on fifteen survivors (8 Malays and 7 non-Malays) obtained from the Oncology and Surgery Department, National University of Malaysia Hospital. The study was conducted using a semi-structured interview format. The data obtained were sorted into various categories via content analysis. Results : Majority of breast cancer survivors increased their fruit and vegetable intake following diagnosis. Some non-Malays changed to vegetarian whereas all the Malays remained on the same dietary pattern. As far as exercise was concerned, all Malays did not exercise before diagnosis, but did so after diagnosis, whereas most of non-Malays did not exercise either before or after diagnosis. Conclusion : Some changes were noticed in dietary and lifestyle behaviors after diagnosis among some survivors. The differences were due to their different cultural and religious backgrounds.